Engineering pichia pastoris as a heterologous platform for non-ribosomal peptide biosynthesis of the β-lactam intermediate δ-(L-α-Aminoadipyl)-L-cysteinyl-D-valine (ACV) - Jogi, Shraddha; Jagtap, Rutuja; Subrahmanyam, Yalamanchili Venkata; Sharma, Monika; Kulkarni, Mahesh; Raghunathan, Anu (ACS Omega, 2026)
The production of nonribosomal peptides (NRPs) in non-native hosts remains challenging due to the size and complexity of the biosynthetic enzymes. Here, we report the first successful reconstruction of the delta-(L-alpha-aminoadipyl)-L-cysteinyl-D-valine (ACV) pathway in Pichia pastoris. By introducing codon-optimized versions of the pcbAB and npgA genes directly into the genome, we were able to rebuild the minimal pathway required for ACV synthesis, which we confirmed using LC-MS/MS. Although the starting strain produced only small amounts of ACV (similar to 5 ng/mL), yields increased 10-fold after adaptive evolution (similar to 50 ng/mL) and further improved with precursor supplementation (similar to 60 ng/mL). Transcriptomic analysis showed that the engineered strain reorganized its metabolism to meet the energy and precursor demands of NRPS activity. Overall, this study suggests that P. pastoris can serve as a practical, proof-of-concept host for complex NRP biosynthesis and lays the groundwork for future engineering of beta-lactam pathways.